Biological activities of polypyridyl-type ligands: implications for bioinorganic chemistry and light-activated metal complexes. (April 2021) - Hachey, Austin C.; Havrylyuk, Dmytro; Glazer, Edith C.
Abstract: Polypyridyl coordinating ligands are common in metal complexes used in medicinal inorganic chemistry. These ligands possess intrinsic cytotoxicity, but detailed data on this phenomenon are sparse, and cytotoxicity values vary widely and are often irreproducible. To provide new insights into the biological effects of bipyridyl-type ligands and structurally related metal-binding systems, reports of free ligand cytotoxicity were reviewed. The cytotoxicity of 25 derivatives of 2, 2′-bipyridine and 1, 10-phenanthroline demonstrates that there is no correlation between IC50 values and ligand properties such as pKa, log D, polarizability volume, and electron density, as indicated by NMR shifts. As a result of these observations, as well as the various reported mechanisms of action of polypyridyl ligands, we offer the hypothesis that biological effects are governed by the availability of and affinity for specific metal ions within the experimental model. Graphical abstract: Image 1